A pair of epimeric cassane-type diterpenoids and a new labdane-type derivative from Caesalpinia decapetala. Issue 28 (12th July 2018) - Qiao, Yuben; Liu, Yanfei; Duan, Xueyan; Chen, Chunmei; Liu, Junjun; Zhu, Hucheng; Xue, Yongbo; Zhang, Yonghui
Abstract: Caesaldecins A and B (1 a/1 b), a pair of epimeric cassane-type diterpenoids containing an ether linkage between C-6 and C-20 and an α, β -butenolide ring in the northern hemisphere, were isolated from the leaves of the medicinal plant Caesalpinia decapetala (Roth) Alston, along with a new labdane-type diterpenoid, termed as 8(17), 11( Z ), 13( E )-trien-15, 18-dioic acid (2 ). Structures of 1 and 2 were established by extensive spectroscopic analyses, including HRESIMS, 1D and 2D NMR, and electronic circular dichroism (ECD) calculations. The in vitro antibacterial and inhibitory activities against a panel of bacteria and cancer cell lines were evaluated, respectively. Compound 2 displayed moderate antibacterial activity against the methicillin-resistant Staphylococcus aureus subsp. aureus (MRSA) with an MIC50 value of 5.99 μg mL −1 . Graphical abstract: Image 1 Highlights: A pair of epimeric cassane and a new labdane diterpenoids were isolated from Caesalpinia decapetala (Roth) Alston. Compounds 1 a/1 b contained an ether linkage between C-6 and C-20 and an α, β -butenolide ring. Compound 2 displayed moderate antibacterial activity against MRSA with MIC50 value 5.99 μg mL −1 .